Improving Students’ Critical Thinking Through Problem-Based Learning in Physics: A Quasi-Experimental Study at SMA Negeri 7 Surakarta - Jihan Fadhilasari; Daru Wahyuningsih (Universitas Sebelas Maret, 2025)
During the Industrial Revolution era, education faced the challenge of equipping students with 21st-century skills, one of which is the ability to think critically. The core of the problem raised is the low critical thinking ability of students and the development of effective learning models to develop them, especially in Physics learning. As a solution, research is carried out to explore the implementation of learning models, primarily Problem-Based Learning. The purpose of this research is to investigate the application of the Problem-Based Learning model on students’ critical thinking skills, assess its effectiveness, and identify both the advantages and disadvantages of the learning model, particularly in dynamic fluid materials. The research was conducted at SMA Negeri 7 Surakarta using a quasi-experimental design involving two groups: an experimental class that implemented the Problem-Based Learning (PBL) model and a control class that employed conventional learning methods. The result of this study shows that the Problem-Based Learning model effectively improves students' critical thinking skills in dynamic fluid physics materials. This study also confirmed a significant rise in students’ critical thinking skills after the application of the Problem-Based Learning model. In conclusion, the Problem-Based Learning model is an effective and pedagogically valuable strategy for enhancing students’ critical thinking skills in Physics